Kajian Antropolinguistik pada Tradisi Ritual Benta-Benti di Dukuh Kalijambe, Desa Cinanas, Bantarkawung, Brebes - Casim Casim; Ghulam Arif Rizal; Savana Fadilatul Sefty; Raudzotu Syaadah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The Benta-Benti ceremonial practice in Dukuh Kalijambe, located in Cinanas Village, Bantarkawung, Brebes, is a cultural custom that continues to be upheld by the local residents. This practice carries significant cultural and spiritual meanings and is vital to the community's daily existence. The purpose of this study is to explore the Benta-Benti ceremonial tradition in Dukuh Kalijambe, Cinanas Village, Bantarkawung, Brebes, through an anthropolinguistic lens. The research utilizes qualitative methods alongside an anthropolinguistic framework. Information was gathered via participant observation, interviews, and textual analysis. Findings from the research reveal that: 1) within the Benta-Benti ceremonial practice in Dukuh Kalijambe, Cinanas Village, Bantarkawung, Brebes, there exist co-texts (such as processes of inheritance, storytelling, and creativity) along with contexts that include ideological, cultural, social, and religious aspects; 2) this tradition is maintained through the languages and means of communication utilized in the ceremonies, including Javanese, Sundanese, and Indonesian; 3) the research also highlights that this tradition affects the community's lives, especially regarding their identity, unity, and faith; 4) the Benta-Benti ritual practice serves as a significant representation of a tradition rich in cultural and spiritual significance.